Frames that Speak Cartouches on Early Modern Maps - Van Duzer, Chet (Brill, 2023)
This lavishly illustrated book is the first systematic exploration of cartographic cartouches, the decorated frames that surround the title, or other text or imagery, on historic maps. It addresses the history of their development, the sources cartographers used in creating them, and the political, economic, historical, and philosophical messages their symbols convey. Cartouches are the most visually appealing parts of maps, and also spaces where the cartographer uses decoration to express his or her interests-so they are key to interpreting maps. The book discusses thirty-three cartouches in detail, which range from 1569 to 1821, and were chosen for the richness of their imagery. The book will open your eyes to a new way of looking at maps.